Enhancing EFL StudentsÔÇÖ Writing Skills Through Blogging in Indonesian Vocational High School - M. Syafi'i; Besral Besral; Yulnetri Yulnetri; Raya Fitri Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study examines the effectiveness of Web Blog (WB) practices in enhancing the foreign language (FL) writing skills of vocational high school students in Indonesia. Digital learning, especially web-learning based blog (WB) has been proven advantageous to enhance the second and foreign language skills of Senior High school and university students in Indonesia. However, little research to date has explored whether Web Blog practices are fruitful for vocational high school learners in foreign language (FL) contexts, a population characterized by low competence levels, naughty adolescents, and few opportunities to engage with the FL. This study involved a tenth-grade class (N=18) who participated in a pre-test, received WB-based instruction, and then completed a post-test. The findings revealed significant improvements in studentsÔÇÖ writing, as evidenced by higher post-test scores in unity, completeness, coherence, and spatial order. The implications of these results suggest that incorporating WB into FL instruction can effectively enhance the writing skills of vocational high school students, providing them with greater opportunity for peer collaboration and teacher-led conferences.